Motivational Domains in Learning and Academic Performances Among Undergraduate Nursing Students of University of Hail, Kingdom of Saudi Arabia - Edison, J. Silvia; Ahmad, Hanan Haj; Sallam, Salwa Abdel Gawad; Alanazi, Aishah Aladham; Alrashidi, Lamya Kalaf (European Journal of Applied Sciences, 2022)
This research studies the relationship between motivational domains and academic performances of nursing students at the University of Hail region, Kingdom of Saudi Arabia. The Methodology is a descriptive cross-sectional study design, and it considers a sample of 86 nursing students enrolled in BSC Nursing during the academic year 2021-2022 at the University of Hail. Regression and correlation analysis are obtained and the main results state that: A positive correlation is established between the domains such as active learning strategies, learning values, performance goal, learning environment stimulation, and self- regularity at 0.05 level of significance, while there is no correlation between the student grade and all the motivational domains at 0.05 level. There was no correlation between the student grade and the motivational domains.